Synaptic inputs and timing underlying the velocity tuning of direction-selective ganglion cells in rabbit retina - Sivyer, Benjamin (Blackwell Science Inc, 2010)
There are two types of direction-selective ganglion cells (DSGCs) identified in the rabbit retina, which can be readily distinguished both morphologically and physiologically. The well characterized ON–OFF DSGCs respond to a broad range of image velocities whereas the less common ON DSGCs are tuned to slower image velocities. This study examined how the synaptic inputs shape the velocity tuning of DSGCs in an isolated preparation of the rabbit retina. The receptive-field properties were mapped by extracellular spike recordings and compared with the light-evoked excitatory and inhibitory synaptic conductances that were measured under voltage-clamp. The synaptic mechanisms underlying the generation of direction selectivity appear to be similar in both cell types in that preferred-direction image motion elicits a greater excitatory input and null-direction image motion elicits a greater inhibitory input. To examine the temporal tuning of the DSGCs, the cells were stimulated with either a grating drifted over the receptive-field centre at a range of velocities or with a light spot flickered at different temporal frequencies. Whereas the excitatory and inhibitory inputs to the ON–OFF DSGCs are relatively constant over a wide range of temporal frequencies, the ON DSGCs receive less excitation and more inhibition at higher temporal frequencies. Moreover, transient inhibition precedes sustained excitation in the ON DSGCs, leading to slowly activating, sustained spike responses. Consequently, at higher temporal frequencies, weaker excitation combines with fast-rising inhibition resulting in lower spike output.